Peculiarities of structure formation during casting of hypereutectic silumin with inverted structure - E. I. Marukovich; V. Ju. Stetsenko; A. M. Branovitskij (Литьë и металлургия)
Peculiarities of structure formation in hypereutectic silumin with inverted microstructure at horizontal continuous casting have been investigated.